ANALISIS TINDAK TUTUR DALAM NOVEL MY LECTURER MY HUSBAND KARYA GITLICIOUS (KAJIAN PRAGMATIK) - Karolina Dawus; Ni Luh Sukanadi; Ida Ayu Made Wedasuwari (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2021)
This research is a descriptive study that aims to describe the types of directive and expressive speech acts in the novel